Driving balancing responsibility: why imbalance pricing methodologies and balancing area sizing matter for renewables - Schwidtal, Jan Marc; Chaves Ávila, José Pablo; Lorenzoni, Arturo (My University, 2021)
With the increasing share of renewable energies in electricity generation and the approaching grid parity of individual resources, full-fledged integration is becoming ever more important. System balance is thereby one of the key challenges that comes along with nonprogrammable resources and which as of now is often provided by conventional resources. Based on an empirical analysis of the Italian electricity market, this article outlines how to enable renewables by turning an onerous cost into an active incentive to support system operation. It sheds light on the implications of different imbalance pricing and settlement schemes to support policymakers in their way to further integrate RES in all system operation and putting them on an equal footing with conventional units. A special focus lies thereby on the underlying design variable of balancing areas, an aspect to which comparably little attention has been paid so far in the academic discussion. To validate the derived implications under different system conditions, the study is extended by a special section with data from the COVID-19 lockdown, representing a period of both increased price competition and renewable share.

With the increasing share of renewable energies in electricity generation and the approaching grid parity of individual resources, full-fledged integration is becoming ever more important. System balance is thereby one of the key challenges that comes along with nonprogrammable resources and which as of now is often provided by conventional resources. Based on an empirical analysis of the Italian electricity market, this article outlines how to enable renewables by turning an onerous cost into an active incentive to support system operation. It sheds light on the implications of different imbalance pricing and settlement schemes to support policymakers in their way to further integrate RES in all system operation and putting them on an equal footing with conventional units. A special focus lies thereby on the underlying design variable of balancing areas, an aspect to which comparably little attention has been paid so far in the academic discussion. To validate the derived implications under different system conditions, the study is extended by a special section with data from the COVID-19 lockdown, representing a period of both increased price competition and renewable share.